Knowledge, Attitude and Practice (KAP) of Laboratory Safety among Laboratory Workers: Knowledge, Attitude and Practice of Laboratory Safety - Imdad, Sana; Dar, Rehma; Akhtar, Raana; Shakoor, Maham; Ali, Moazem; Asif, Muhammad; Ashraf, Sobia (Pakistan Journal of Health Sciences, 2024)
Clinical laboratories have an essential part in the diagnosis of disease. However, they also pose several hazards, including exposure to infectious agents, chemicals and radiation, as well as physical hazards such as ergonomic injuries. Adequate safety measures must be designed and practiced to minimize the risk of hazards and make sure the safety of laboratory workers. Objectives: To assess Knowledge, Attitude and Practice of Laboratory Safety among laboratory workers. Methods: It was an observational cross-sectional study conducted over two months in all the affiliated laboratories of Mayo Hospital, Lahore. The questionnaire regarding Knowledge, Attitude and Practice regarding Laboratory Safety was filled by 75 participants. All the collected data were analyzed using SPSS 23. The qualitative variables were mentioned as frequency and percentage and the quantitative variables as mean ± SD. Results: Out of 75 participants, 59% were male and 41% were female. The Knowledge, Attitude and Practice scores were 23.15 ± 2.88, 11.0 ± 1.26 and 11.73 ± 1.97 respectively. The job title was associated with knowledge significantly (p= 0.03) and practice level (p=0.01). The participants’ knowledge was significantly correlated with attitude (r=0.341, p=0.003) and practice (r=0.379, p=0.001). Conclusions: It was concluded that the laboratory workers had overall excellent knowledge, good attitude and practice level. The job title had a significant association with knowledge and practice level. The correlation of knowledge with attitude and practice was significant